2019
DOI: 10.1016/j.jcmg.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography for the Early Detection of Coronary Vascular Changes in Children and Adolescents After Cardiac Transplantation

Abstract: OCT provides important insights into coronary vascular changes not detected by angiography in pediatric transplant recipients. The use of OCT for pediatric heart transplant recipients should be further investigated, given its potential to impact the management of CAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…Previous studies showed that excessive intimal thickening is the first step in coronary pre-atherosclerosis, preceding lipid deposition [ 31 33 ]. Indetectable but important, therefore, the IMR has been widely used for evaluating the severity of intimal hyperplasia [ 13 , 14 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that excessive intimal thickening is the first step in coronary pre-atherosclerosis, preceding lipid deposition [ 31 33 ]. Indetectable but important, therefore, the IMR has been widely used for evaluating the severity of intimal hyperplasia [ 13 , 14 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OCT images were analysed as previously described. 29 For each pullback, digital planimetry of nine cross-sectional frames at least 1 mm apart was performed. Intimal thickness was determined, and the I/M CSA ratios were calculated (Figure 1).…”
Section: Cavmentioning
confidence: 99%
“…This recommendation has increasingly led to using intravascular imaging techniques such as OCT to supplement the information obtained from conventional coronary angiograms. In pediatric cardiology, there has been increasing interest in the use of OCT for evaluating coronary anatomy in patients with Kawasaki disease and post–heart transplantation ( 7 , 8 , 9 ). Our case shows the potential for using OCT as an adjunct to conventional cardiac imaging for surveillance of coronary stents in pediatric patients.…”
Section: Question 3: How Should Coronary Stents Be Monitored For Stent Failure In Pediatric Patients?mentioning
confidence: 99%